Evolutionary history of the kelp gull (Larus dominicanus) at the south hemisphere supported by multilocus evidence - de Almeida Santos, Fernanda; Stenghel Morgante, João; Frere, Esteban; Millones, Ana; Sander, Martin; de Abreu Vianna, Juliana; Pires de Mendonça Dantas, Gisele (Journal of Ornithology)
The high dispersal ability of seabirds and theabsence of geographical barriers has led to high gene flowand reduced population differentiation. Nevertheless, somespecies with philopatric behavior have restricted gene flowamong colonies, revealing a strong population structure.Gulls show widespread colonial behavior, and are longlivedspecies, which make them a good model for understandingevolutionary processes in seabirds. Previousgenetic studies on the Kelp Gull (Larus dominicanus) haverevealed low genetic variability in mitochondrial markersbut relatively high genetic variation in a nuclear marker.These observations can be explained by the occurrence of aselective sweep on mtDNA, population genetic bottlenecksor a recent origin of the species. We used microsatellitedata to further investigate these hypotheses, mainly bytesting for bottleneck events. Low genetic variability(Ho = 0.276?0.570) was detected in Kelp Gulls. However,population genetic structure was observed among regions(Chile, Argentina and Brazil), and between continents(South America and Antarctica). The population of theKelp Gull in South America may have differentiated due toisolation by distance (r = 0.7273, p = 0.0013), whereasthe population in the Antarctic seems to be isolated by nonphysicalbarriers. Bottleneck events were detected in 6 outof 14 colonies studied. These colonies are at the limits ofthe distribution of the Kelp Gull, and thus experience harshsurvival conditions. We believe that the Kelp Gull has acomplex history in the southern hemisphere, with a recentorigin, followed by bottlenecks and then population expansion. Thus, the genetic diversity found in Kelp Gull issimilar to that observed for other species of Laridae. Fil: de Almeida Santos, Fernanda. Universidade de Sao Paulo; Brasil Fil: Stenghel Morgante, João. Universidade de Sao Paulo; Brasil Fil: Frere, Esteban. Universidad Nacional de la Patagonia Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Millones, Ana. ...